Variants in CFTR untranslated regions are associated with congenital bilateral absence of the vas deferens. Issue 3 (23rd October 2010) - Lopez, Estelle; Viart, Victoria; Guittard, Caroline; Templin, Carine; René, Céline; Méchin, Déborah; Georges, Marie Des; Claustres, Mireille; Romey-Chatelain, Marie-Catherine; Taulan, Magali
Abstract : Background: Congenital bilateral absence of the vas deferens (CBAVD), a frequent cause of obstructive azoospermia, is generated by mutations in the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene. Despite extensive testing for point mutations and large rearrangements, a small proportion of alleles still remains unidentified in CBAVD patients. Methods and results: Mutation scanning analysis of microsatellite variability in the CFTR gene identified two undescribed 4 bp sequence repeats (TAAA)6 and (TAAA)8 in intron 9 in two CBAVD patients heterozygote for either the −33G→A promoter transition or the classical [TG12T5] CBAVD mutation. This study explores the putative impact of this promoter variant by using a combination of web based prediction tools, reporter gene assays, and DNA/proteins interaction analyses. Results of transiently transfected vas deferens cells with either the −33G wild-type or the −33A variant CFTR directed luciferase reporter gene confirmed that the −33A variant, which alters the FOXI1 (Forkhead box I1) binding, significantly decreases the CFTR promoter activity. It was also investigated whether regulatory elements located within the intronic tetrarepeat might influence the CFTR expression. There was evidence that both the (TAAA)6 and the (TAAA)8 alleles modulate the CFTR transcription and the binding affinity for FOX transcription factors, involved in the chromatin architecture. Conclusions: As the vas deferens seems to be one of the tissues most susceptible to a reduction in the normal CFTR transcripts levels, and as two mild mutations are sufficient to induce CBAVD phenotype, these findings raise the possibility that these uncommon variants may be a novel cause of CBAVD.